Impact of the implementation of multimedia content as a strategy for the creation of inclusive digital courses - Navarro Suárez, Armando (Nawi, 2023)
This research reflects on the communicative processes and technological means within the educational field. It takes as a starting point the generalities of society and its new forms of technological interaction, their impact on teaching processes and, in turn, the impact on the generation of inclusive courses. Particular aspects of the new teaching practices are highlighted, as well as the role of the student, in order to subsequently analyse the impact of ICT-based teaching processes in our society.
Keywords: Multimedia; inclusion; education; strategies; digitization; ICTs